Guttiferone E Displays Antineoplastic Activity Against Melanoma Cells - Ribeiro, Arthur Barcelos; Nicolella, Heloiza Diniz; da Silva, Lucas Henrique Domingos; Mejía, Jennyfer Andrea Aldana; Tanimoto, Matheus Hikaru; Ambrósio, Sérgio Ricardo; Bastos, Jairo Kenupp; Orenha, Renato Pereira; Parreira, Renato Luis Tame; Tavares, Denise Crispim (Planta Medica, 2022)
Guttiferone E (GE) is a benzophenone found in Brazilian red propolis. In the present study, the effect of GE on human (A-375) and murine (B16-F10) melanoma cells was investigated. GE significantly reduced the cellular viability of melanoma cells in a time-dependent manner. In addition, GE demonstrated antiproliferative effect, with IC50 values equivalent to 9.0 and 6.6 µM for A-375 and B16-F10 cells, respectively. The treatment of A-375 cells with GE significantly increased cell populations in G0/G1 phase and decreased those in G2/M phase. Conversely, on B16-F10 cells, GE led to a significant decrease in the populations of cells in G0/G1 phase and concomitantly an increase in the population of cells in phase S. A significantly higher percentage of apoptotic cells was observed in A-375 (43.5%) and B16-F10 (49.9%) cultures after treatment with GE. Treatments with GE caused morphological changes and significant decrease to the melanoma cellsʼ density. GE (10 µM) inhibited the migration of melanoma cells, with a higher rate of inhibition in B16-F10 cells (73.4%) observed. In addition, GE significantly reduced the adhesion of A375 cells, but showed no effect on B16-F10. Treatment with GE did not induce changes in P53 levels in A375 cultures. Molecular docking calculations showed that GE is stable in the active sites of the tubulin dimer with a similar energy to taxol chemotherapy. Taken together, the data suggest that GE has promising antineoplastic potential against melanoma.
Keywords: Benzophenone; Brazilian red propolis; cell cycle; apoptosis; P53